The role of client participation and psychological comfort in driving perceptions of audit quality: Evidence from an emerging economy. Issue 2 (7th May 2019) - Sampet, Jomjai; Sarapaivanich, Naruanard; Patterson, Paul
Abstract : Purpose: With increased competition under the establishment of the ASEAN Economic Community (AEC) in December 2015, CPA and Tax Auditors are free to export their services within AEC partner countries. Hence, it is crucial that the growing numbers of auditors in the region differentiate themselves by providing superior perceived audit quality and client value in order to retain (and attract) clients. Based on theoretical foundations of service-dominant logic and culture theory, the purpose of this paper is to investigate the role of client involvement in the audit process and client psychological comfort in influencing client perceptions of audit quality. Design/methodology/approach: A survey was used to collect data from firms listed on the Thai Stock Exchange. The unit of analysis was the client firm. A key informant method was used whereby a senior manager, heavily involved in the auditor assessment and selection process answered all questions on behalf of their company. Data from 190 firms are subsequently analyzed with structural equation modeling. Findings: Both client level of involvement and psychological comfort impact their perceptions of three dimensions of audit quality: service quality, independence and competence. Audit quality in turn is strongly associated with overall client satisfaction. Originality/value: While various scholarly works have examined audit quality, this study does so in an emerging, highly collectivist culture (Thailand) where due to cultural norms, relationships take on added importance. More importantly, for the first time, the study shines the spotlight on the role that client involvement in the audit process, and client psychological comfort, play in influencing client perceptions of audit quality.